The influence of increasing temperatures on highland barley yields and on the maximum cultivation altitude on the Tibetan Plateau - Chun-Yi Wang; Yan-Ling Song; Hans W. Linderholm; Yong Li; Bo-Ting Zhang; Jun Du; Feng-Xia Li; Ming-Tian Wang; Run-Yuan Wang; Yong Zhu; Jin-Xia Xu; Yan-Jun Guo; et al. (Advances in Climate Change Research, 2023)
Highland barley (Hordeum vulgare Linn. cv. nudum Hook. f.) is the principal cereal crop over the Tibetan Plateau (TP). The response of highland barely to climate change in the past decades, especially in terms of yields still remains uncertain. In this study, its responses to climate change were investigated using daily weather data and agriculture data during 1961–2018. The results showed that the annual mean air temperature over the TP increased at 0.33 °C per decade during 1961–2018, and the rate of warming increased with altitude, reaching 0.41 °C per decade at altitudes of 4500–4700 m. The growing degree days (GDDs) increased by 9.6% during 2011–2018 compared with the 1960s, whereas low temperature degree days (LDDs) decreased by 40.3% over the same period, indicating that the thermal conditions for highland barley cultivation have improved. A strong relationship was observed between the yield of highland barley and LDDs (−0.76, p < 0.001) than GDDs (0.58, p < 0.001) in Xizang, where sufficient irrigation water is available from the melting of snow cover or glaciers. In Sichuan, with abundant precipitation, significant correlations were noticed between county-level barley yield and GDDs and LDDs (0.60, p < 0.001; −0.65, p < 0.001). In Qinghai, the dry regions, county-level yields were influenced significantly by temperature and precipitation. These results indicated that climate warming was beneficial to highland barley yield in most region of the TP, mainly due to decreased LDDs. The potential altitude at which highland barley cultivation is feasible increased by approximately 280–484 m during 2016–2018, compared with 1981–1983. In Xizang, highland barley could be cultivated up to an altitude of 4507 m a.s.l. between 2016 and 2018, and it increased to 4179 m a.s.l. in Qinghai. These results could help local government to take actions to adapt to global warming and improve food security.